From Strategy to Practice: A Roadmap for Implementing an Integrated Dormitory Curriculum for I’dadiyah Students in Islamic Boarding Schools - Muhammad Zaki Maulana; Mohammad Rifai (Al-Qalam Institue, 2025)
The purpose of this study is to explore strategic approaches for implementing and optimizing a dormitory-based curriculum while designing a practical learning roadmap for new I’dadiyah students. Unlike conventional education, the dormitory curriculum emphasizes not only academic achievement but also character building and essential life skills. Adopting a case study design with a qualitative approach, data were collected through observation, in-depth interviews, and document analysis related to the I’dadiyah dormitory program. The findings highlight the importance of synergy among administrators, educators, and students, supported by a structured learning roadmap. This roadmap outlines three key stages: adaptation, reinforcement of basic competencies, and personal development. By integrating holistic learning methods with continuous evaluation, the dormitory curriculum can be effectively optimized to foster both intellectual and moral growth. The study concludes by recommending the strengthening of monitoring and evaluation systems as well as the active engagement of all stakeholders. Such strategic implementation ensures that the dormitory curriculum functions not merely as an academic framework but as a transformative model for cultivating well-rounded, resilient, and capable students in the pesantren environment.